PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA ELEMEN DASAR POLA FASE E DI SMK NEGERI 2 LUMAJANG - Setyaningrum, Ayu Intan Permatasari Kurnia; Nahari, Inty; Rahayu, Imami Arum Tri; Yuniati, Mita (Jurnal Socia Akademika, 2023)
The research objectives include 1) knowing the application of the Problem Based Learning learning model to the Basic Pattern elements of stage E class 2 Lumajang. This type of research is quantitative research with a pre-experimental design and a one shot case study model. This research was carried out at SMK Negeri 2 Lumajang in class X Fashion Design and Production 2, totaling 20 students. There are two data collection methods, namely observation to determine the application of the Problem Based Learning learning model to the basic elements of body measurement patterns, and tests to determine the effectiveness of the application of the learning model on student learning outcomes. The results of the research state that the application of the Problem Based Learning learning model can be seen from the application of the learning model to the basic elements of pattern material, carrying out actions so as to obtain an average score of 3.7 for teacher activities very well. criteria and the average student activity score is 3.4 with good criteria. Student learning outcomes on the cognitive test obtained an average score of 81.5 and the average score on the psychomotor test obtained an average score of 87.5. The overall average score for student learning outcomes is 86.4, which is declared as having completed the KKM. As many as 85% of students completed the KKM and 15% did not complete the KKM.